Hybrid MPPT technique using fuzzy logic and P&O of solar power system - Et-Torabi, Karima; Barakat, Souhail; N’hili, Badr; Mesbahi, Abdelouahed; Nouaiti, Ayoub (Institute of Advanced Engineering and Science, 2025)
This paper introduces an enhanced perturb and observe (P&O) technique with a variable step size utilizing fuzzy logic to address the limitations of the traditional P&O technique, particularly under rapidly fluctuating solar radiation conditions. The performance of the suggested variable step size FLC-P&O maximum power point tracking (MPPT) and the constant step size P&O techniques is simulated and evaluated under various operating scenarios using MATLAB/Simulink software. The suggested technique was successfully validated using a boost converter connected to a Canadian Solar CS6P-240P photovoltaic (PV) model. The results demonstrate that the FLC P&O technique improves response accuracy and reduces steady-state terminal voltage fluctuations. Moreover, the findings show that the suggested technique provides a faster response and higher MPPT efficiency compared to the traditional P&O technique, particularly during sudden variations in solar irradiance.